2017
DOI: 10.17265/2159-5828/2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Peptides Obtained from Cotton Ground Oil-Cake Proteins

Abstract: Antioxidant activity of the peptides derived from proteins of defatted cottonseed kernels and cotton ground oil-cake by their enzymatic hydrolysis with acidic (Asp. niger) and neutral proteinases (Bac. amyloliquefaciens) was studied. Antioxidant activity of the derived peptides depended on the used proteins and enzymes. The peptides derived by using of neutral proteinase possessed higher antioxidant activity, in comparison with the peptides derived by acidic proteinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Cakes, for themselves, present high antioxidant activity [7]. The high antioxidant activity of JSC is attributed to high concentrations of phenolic compounds [41] and, in CSC due to the presence of peptides with antioxidant activity, which reduces catechin oxidation [42] and the presence of secondary metabolites such as gossypol [43]. Guimarães et al [41] observed a reduction of 97.8% of the antioxidant activity in JSC and CSC after 15 days of macrofungi fermentation.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%
“…Cakes, for themselves, present high antioxidant activity [7]. The high antioxidant activity of JSC is attributed to high concentrations of phenolic compounds [41] and, in CSC due to the presence of peptides with antioxidant activity, which reduces catechin oxidation [42] and the presence of secondary metabolites such as gossypol [43]. Guimarães et al [41] observed a reduction of 97.8% of the antioxidant activity in JSC and CSC after 15 days of macrofungi fermentation.…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%